X-ray diffraction, spectroscopic and mechanical studies on potential organic NLO materials of metaNitroaniline and N-3-Nitrophenyl Acetamide single crystals. Issue 1 (17th February 2015) - Senthil, S; Madhavan, J
Abstract: In the present paper, attempts were made to grow good quality metaNitroaniline (mNA) and N-3-Nitrophenyl (3-NAA) single crystals. The lattice parameter values from the Powder X-ray diffraction pattern confirms that mNA belongs to orthorhombic crystal system with the unit cell parameter values of a = 6.501 Å, b = 19.330 Å and c = 5.082 Å with space group Pbc21 . Similarly the powder XRD data indicates that 3-NAA crystal retained its monoclinic structure with lattice parameter values a = 9.762 Å, b =13.287 Å, c =13.226 Å, and β = 102.99°. Investigation has been carried out to assign the vibrational frequencies of the grown crystals by Fourier Transform infrared spectroscopy technique. The SHG efficiency of mNA and 3NAA was determined by Kurtz and Perry powder technique. The Optical absorption study confirms the suitability of the crystals for device applications. The mechanical properties of the grown crystals have been studied using Vickers microhardness tester.